Acute biliary conditions in geriatrics: analysis of 151 observations, clinical and diagnostic concepts - Mesa, Guillermo; Piacenza, Guillermo; Araújo, Raquel (Cirugía del Uruguay, 1975)
The authors performed a diagnostic review of 151 paticnts older than 65 who presented non-neoplasic acute biliary processes. The most frequent clinical findings were discussed , pointing out: the poor simptomatology reiated to the magnitude of the surgical findings; the high nccurrence of signs of participation of the common bile duct (2 0 % of choledocholitiasis), the frequent eariy peritoneal involvement (9 % of the cases), so frequently ignored ( 7 cases out of 16). and the high incidence of associated affections (s pecially cardiovascula r ailments and d;abetes), which compel to an early surgery in order to correct the imbalance the acute biliary affection means far them.